2022
DOI: 10.1021/acs.iecr.2c01334
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of Gas–Liquid Mass-Transfer Efficiency by Introducing a Superaerophilic Surface in the Ozonation Process

Abstract: Wastewater treatment by ozonation has the advantage of strong oxidizing ability and no secondary pollution. However, the mass-transfer resistance of the gas–liquid interface makes this process less efficient. In this work, a superaerophilic surface was introduced to solve this problem. It was confirmed that the superaerophilic surface could improve the liquid phase mass-transfer coefficient (K L) based on its super affinity to gas through the single board experiment. Moreover, aeration experiment showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The first one is related to the poor ozone gas/liquid mass transfer and a low ozone utilization rate when treating wastewater [12][13][14]. As ozone gas generation is an energy-intensive process, this reduces the cost-effectiveness [15,16]. Besides, the low ozone mass transfer from gas phase to liquid phase limits the organic compounds degradation in solution [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one is related to the poor ozone gas/liquid mass transfer and a low ozone utilization rate when treating wastewater [12][13][14]. As ozone gas generation is an energy-intensive process, this reduces the cost-effectiveness [15,16]. Besides, the low ozone mass transfer from gas phase to liquid phase limits the organic compounds degradation in solution [17].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the low ozone mass transfer from gas phase to liquid phase limits the organic compounds degradation in solution [17]. As such, solving the mass transfer problem and achieving high degradation efficiency of target pollutants at low energy consumption becomes a key to reducing the cost of the ozonation process [15]. A previous study showed that adding two minerals (i.e.…”
Section: Introductionmentioning
confidence: 99%